A Multimodal Analysis of the Brave Pink and Hero Green Phenomena on Social Media: A Social Semiotic Study - iif Ifhamuddin; Budi Hermawan; Neidya Fahma Sunendar (Journal of Pragmatics Research, 2026)
This study aims to analyze the construction of identity and ideology through multimodal representations in the phenomena of Brave Pink and Hero Green within the digital public sphere, particularly in posts shared on Instagram and Twitter/X. The dataset consists of three social media posts: two from Instagram and one from Twitter/X. Employing a qualitative approach, this study applies multimodal analysis to visual and verbal data collected from social media posts. The analysis is grounded in Kress and van Leeuwen's theory of multimodality, Halliday's metafunction framework, and critical ideology theory to reveal the role of color as a semiotic resource in meaning-making. The findings indicate that Brave Pink constructs an identity of courage that is inclusive, empathetic, and capable of challenging traditional stereotypes of femininity. Meanwhile, Hero Green represents the heroism of ordinary people through narratives of solidarity, sacrifice, and resistance against injustice. The color green functions not only as a marker of the identity of online motorcycle taxi (ride-hailing) drivers but also as a symbol of respect for victims and a representation of criticism toward power relations and the violence experienced by vulnerable groups. These two phenomena demonstrate that color serves not merely as an aesthetic element but also as a symbolic device that frames social narratives, fosters collective solidarity, and becomes a site for negotiating ideological values in digital culture. Furthermore, this study shows that the meaning of color is dynamic and continuously produced through the interaction of multiple modes, including text, visuals, and social context. Therefore, multimodal analysis is essential for understanding contemporary representational practices and the role of color in mediating the construction of identity, solidarity, power relations, and ideology in the digital era.